Health conditions of elderly in Primary Health Care - Cenir Gonçalves Tier; Silvana Sidney Costa Santos; Marcia Adriana Poll; Roberta Medeiros Hilgert (Rev Rene)
This study aimed to identify the health conditions and environmental factors that influence the activities of daily living of elderly people. Cross-sectional epidemiological research conducted with 167 elderly in a municipality of Rio Grande do Sul, Brazil, from May to July 2013, using a structured instrument. Data were grouped for statistical/descriptive treatment. Circulatory diseases were the most frequent. The commonly used drug was aspirin, and falls were prevalent in 65 elderly. There was a significant difference in eating in age group older than 80 years (p=0,002). Dressing had significance in the age group above 80 years old (p=0.010), but was not significant when associated architecture with age. It was concluded that knowledge of the socio-demographic and health characteristics of the elderly enables the implementation of specific actions by health professionals, besides helping managers to formulate health indicators.